Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-3 Multipying Powers with the Same Base - Practice and Problem-Solving Exercises - Page 431: 68



Work Step by Step

(i) $x^m \cdot x^n = x^{m+n}$ (ii) $x^{-m} = \dfrac{1}{x^m}, x \ne 0$ Use rule (i) above to obtain: $=(a+b)^{2+(-3)} \\=(a+b)^{-1}$ Use rule (ii) above to obtain: $=\dfrac{1}{a+b}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.